Construction of A Novel 2D/1D/‐2D RP/BP‐Bi2WO6 Composite with In Situ Junction and Z‐scheme System for Enhanced Photocatalytic H2 and H2O2 Production. Issue 11 (22nd March 2023) - Zeng, Yating; Fu, Hanping; Liu, Liran; Feng, Li; Zhang, Tianxiang; Liang, Qingshuang; Xiao, Xiufeng
Abstract: Exploring multifunctional photocatalysts with rational design and construction of unique transport channels is of great significance for the value‐added chemicals production and environmental remediation. In this work, a novel 2D/1D/‐2D RP/BP‐MBWO dual heterostructure photocatalyst has been successfully synthesized by loading the in‐situ grown 2D/1D RP/BP heterostructure on the 2D Bi2 WO6 nanosheets. through simple ultrasonic agitation.Benefiting from this favourable interfacial and structural characteristics, the fabricated BP/RP‐MBWO photocatalyst shows a sharply improved photocatalytic H2 and H2 O2 evolution performance. Excitingly, the optimal of H2 O2 production rate of the BP/RP‐Bi2 WO6 composites is as high as 622.5 μmol g −1 h −1 under visible light irradiation, which is approximately 15 times as that of pure MBWO. The hydrogen production performance of the complexes was significantly improved compared to the pure MBWO samples. When the BP/RP loading was 20 %, the prepared nanocomposites showed the highest photocatalytic hydrogen evolution efficiency with the hydrogen production rate of about 0.77 μmol ⋅ g −1 ⋅ h −1 . This work is expected to offer a new inspiration for the rational design and construction of effcient photocatalyst systems toward solar energy capture and conversion. Abstract : A novel 2D/1D/‐2D RP/BP‐MBWO composed of in situ junction and Z‐scheme system has been successfully synthesized. Benefiting from this favourable interfacial and structural characteristics, the fabricated BP/RP‐MBWO photocatalyst shows a sharply improved photocatalytic H2 and H2 O2 evolution performance.